ENGINE PERFORMANCE COMPARISON BETWEEN VARIOUS RON97 GASOLINE BRANDS AVAILABLE IN MALAYSIAN MARKET - Riduan, A.F.M.; Tamaldin, N.; Yamin, A.K.M.; Sudrajat, A. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Disparities towards engine performance by various gasolines from different fuel producers have constantly been a discussion among road users and available information regarding it are still not conclusive. Thus, this paper centres upon examining several Research Octane Number (RON) 97 fuel products sold in Malaysia and determining the key variation among them towards engine outputs. Specific energy was firstly collected using an oxygen bomb calorimeter since it was identified as a main petrol component that could affect overall engine performance. In terms of engine outputs, power break specific fuel consumption (BSFC), and engine efficiency were gathered by experimenting RON97 gasolines with a test engine connected to an engine dynamometer. Outcomes had depicted engine performance from utilizing various petrol products to be dissimilar even though all fuels were evaluated in similar octane rating. It was also found that gasoline specific energy values played a major role towards improving overall engine performance output especially in terms of BSFC (up to 18.47% difference) and engine efficiency (up to 11.67% difference). Therefore, despite fuel calorific value only differs among one and another by a margin lesser than 1%, it had shown towards reducing petrol consumption with up to more than ten times the impact.